2005
DOI: 10.2114/jpa.24.573
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Levels of Elite Endurance Runners after Heavy Endurance Training

Abstract: A decrease in testosterone levels and an increase in cortisol levels are observed in male athletes with the overtraining syndrome (OTS). Cortisol causes blood leptin levels to rise and testosterone has an inverse relationship with blood leptin levels. Therefore, we hypothesized that the hormonal changes as a result of OTS induce an increase in leptin. To test this hypothesis, we examined the relationship among changes in leptin, testosterone and cortisol in thirteen male collegiate distance runners (aged 20.3Ϯ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…However, accounting for changes in body composition, short-term training studies did not demonstrate significant differences in leptin concentrations [207,208].…”
Section: Role Of Leptin In Exercise and The Sympathetic Nervous Systemmentioning
confidence: 89%
“…However, accounting for changes in body composition, short-term training studies did not demonstrate significant differences in leptin concentrations [207,208].…”
Section: Role Of Leptin In Exercise and The Sympathetic Nervous Systemmentioning
confidence: 89%
“…Nonetheless, there was a significant correlation between BMI and average running speed indicating that 10 -12% of the variation in running speed is accounted for by BMI. Studies reporting BMI data for elite adult runners at the middleto marathon-distances have suggested that men average around 19.0 to 21.8 kg • m -2 [1,3,4,8,9,15,17,20,22] and women average around 17.3 to 19.8 kg • m -2 [5,17,22,24,25]. Such values for men appear within the same range as the limited BMI data previously reported for top-level ultramarathon runners of around 21.4 to 21.9 kg • m -2 [5 -7].…”
mentioning
confidence: 99%
“…A diferencia de lo descrito en otros estudios desarrollados en ratas con protocolos de ejercicio a intensidad moderada (Ishigaki, Koyama, Tsujita, Tanaka, Hori, y Oku, 2005; Lira, Rosa, Pimentel, Tarini, Arida, Faloppa, Alves, do Nascimento, Oyama, Seelaender, de Mello, y Santos, 2010), hemos detectado valores adversos en algunos marcadores de perfil lipídico en el grupo de EAI, como mayor colesterol LDL plasmático y mayores concentraciones de grasa en hígado. Tan solo los triglicéridos, presumiblemente por ser la principal fuente energética en el ejercicio, han sido menores en el grupo de ratas de EAI con respecto a las sedentarias.…”
Section: Discussionunclassified